Developmentally regulated expression of integrin alpha-6 distinguishes neural crest derivatives in the skin - Ma, Shize; Li, Xiu; Cao, Rui; Zhan, Guoqin; Fu, Xin; Xiao, Ran; Yang, Zhigang (Frontiers in Cell and Developmental Biology, 2023)
Neural crest-derived cells play essential roles in skin function and homeostasis. However, how they interact with environmental cues and differentiate into functional skin cells remains unclear. Using a combination of single-cell data analysis, neural crest lineage tracing, and flow cytometry, we found that the expression of ITGA6 in neural crest and its derivatives was developmentally regulated and that ITGA6 could serve as a functional surface marker for distinguishing neural crest derivatives in the skin. Based on the expression of ITGA6, Wnt1-Cre lineage neural crest derivatives in the skin could be categorized into three subpopulations, namely, ITGA6bright, ITGA6dim, and ITGA6neg, which we found to be Schwann cells, melanocytes, and fibroblasts, respectively. We further analyzed the signature genes and transcription factors that specifically enriched in each cell subpopulation, as well as the ligand or receptor molecules mediating the potential interaction with other cells of the skin. Additionally, we found Hmx1 and Lhx8 is specifically expressed in neural crest-derived fibroblasts, while Zic1 and homeobox family genes in mesoderm-derived ones, indicating the distinct development pathways of fibroblasts with different origin. Our study provides insight into the regulatory landscape of neural crest cell development and identified potential markers that will facilitate the isolation of different neural crest derivatives in the skin.